KOMODIFIKASI KONTEN TELEVISI DALAM PERSPEKTIF EKONOMI POLITIK MEDIA - MANGGAGA, INDAH PRATIWI (Jurnal Dakwah Tabligh, 2019)
The process of commodification is associated with the product or in this case is the content of television. One of the characteristics of mass media institution is the media related to the industrial market, due to the reliance on employment, technology, and financing needs. Commodification of television contents as the form of hyper-commercialism and rating is the issue of capitalism related to media logic. To see TV content commodification through the perspective of political economy that is stressed about social relations, especially the power relations of mutual benefit of of the sources of production, distribution and consumption, including the communication sources.